2004
DOI: 10.1021/ja0477367
|View full text |Cite
|
Sign up to set email alerts
|

AuBr3-Catalyzed [4 + 2] Benzannulation between an Enynal Unit and Enol

Abstract: The reaction of enynals 1, including o-alkynylbenzaldehydes, and carbonyl compounds 2 in the presence of a catalytic amount of AuBr3 in 1,4-dioxane at 100 degrees C gave the functionalized aromatic compounds 3 in high yields. The AuBr3-catalyzed formal [4 + 2] benzannulation proceeds most probably through the coordination of the triple bond of 1 to AuBr3, the formation of a pyrylium auric ate complex via the nucleophilic addition of the carbonyl oxygen atom, the reverse electron demand-type Diels-Alder additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
43
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(49 citation statements)
references
References 11 publications
5
43
1
Order By: Relevance
“…For this NMR study, the reaction was carried out in the absence of tetrafluoroboric acid; thus, 1 b (1 equiv) was added to a solution of IPy 2 BF 4 (1 equiv) in CD 2 Cl 2 and 1 H and 13 C NMR spectra were recorded at 25 8C after different reaction times (Figure 2). [43] After 6 h, a complete transformation of 1 b (Figure 2, spectrum A) into the corresponding adduct resulting from the incorporation of pyridine into the benzo[c]pyrilium cation I (Figure 2, spectrum B) was observed.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
See 1 more Smart Citation
“…For this NMR study, the reaction was carried out in the absence of tetrafluoroboric acid; thus, 1 b (1 equiv) was added to a solution of IPy 2 BF 4 (1 equiv) in CD 2 Cl 2 and 1 H and 13 C NMR spectra were recorded at 25 8C after different reaction times (Figure 2). [43] After 6 h, a complete transformation of 1 b (Figure 2, spectrum A) into the corresponding adduct resulting from the incorporation of pyridine into the benzo[c]pyrilium cation I (Figure 2, spectrum B) was observed.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…[11] Furthermore, electron-rich heteroaromatic compounds [12] were also shown to be active components for those reaction sequences, as was, remarkably, the enol form in equilibrium with common carbonyl precursors. [13] More recently, fully intramolecular versions of these transitionmetal-catalyzed [4 + 2] benzannulation reactions of alkynyl and alkenyl enynones and enynals have been disclosed, overall giving rise to a powerful and attractive entry for constructing polycyclic hydrocarbons. [14] Among all these studies, the initial formation of the ate isobenzopyrylium complex [15] shown in Scheme 1 (path b) was invoked.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used catalytic systems for the Sonogashira 4 ] together with CuI as the co-catalyst, and large amounts of amines as the solvents or co-solvents. [10] Taking into account that gold has been successful for performing the same role as Pd during carbon-carbon bond formation in the Suzuki-Miyaura condensation, [11] while Au I has the same d 10 electronic structure as Cu I and can easily and properly interact with the acetylenic group, [12] it appeared to us that gold could catalyze the copper-free Sonogashira crosscoupling reaction. In order to explore this possibility, we chose a solid catalyst formed by gold supported on nanocrystalline CeO 2 (Au/CeO 2 ).…”
mentioning
confidence: 99%
“…Gold-catalyzed and/or copper-catalyzed benzannulation reactions between orthoalkynylbenzaldehydes 22 and alkynes gave naphthyl carbonyl compounds 23 in high to good yields (Scheme 7). [91][92][93][94][95][96][97] Coordination of -electrophilic gold to the CC triple bond, followed by addition of carbonyl oxygen to electron deficient triple bond, produces benzopyrylium intermediate 24, which undergoes [4+2] cycloaddition with alkynes as shown in 25. Bond rearrangement in 26 affords 23 and regenerates gold catalyst.…”
Section: Scheme 5 Indene Synthesis Via C-o Bond Additionmentioning
confidence: 99%